Shifting the Urgency of the Inclusion of Variety of Qirā’at in the Interpretation Literature - Lilik Ummi Kaltsum (Dialogia: Islamic Studies and Social Journal, 2021)
This article examines the shift in the urgency of qirā’at, where the author finds a lot of qirā’at content in both classical, modern and contemporary tafseer literature, as well as the causes and effects of the decrease in the quantity of inclusion of various qirā’at in the tafsir literature. In this case, this study analyzes the function and influence of the inclusion of qirā’at in the interpretation process. This method is also used to find out what factors cover each interpreter to include or not include various qirā’at in the work of interpretation. So, this study aims to prove the shift in the urgency of inclusion of qirā’at variants in the tafseer literature; and finding the main factors and impacts of the shift in urgency of inclusion of qirā’at variants in classical, modern, and contemporary interpretation literature. Thus, the main problem that will be examined is how the quantity of qirā’at variety in the tafsir literature and what are the causes and impacts?